Bioassay-Guided Fractination of Antimitotic Compound from Ongkea Cortex (Mezzettia parviflora Becc) Towards Sea Urchin Eggs - Muh. Akbar Bahar; Gemini Alam; Marianti A. Manggau; Mufidah Mufidah; Suparman Suparman (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2015)
Ongkea cortex, the wood bark of Mezzettia Parviflora Becc, is a traditional medicine originated from Southeastern Sulawesi (Indonesia). It has been empirically known to have antitumor property. In this study, we examined the antiproliferative activity and obtained the antimitotic compound of ongkea cortex. Antimitotic activity was ultimately determined by the inhibition of cleavage-stage of newly fertilized sea urchin (Lytechinus variegatus) eggs. A bioassay-guided fractination was performed in order to find the bioactive substance of ongkea cortex. The IC50 values of methanolic extract, ethyl acetate-soluble part of metanolic extract and ethil acetat insoluble part of metanolic extract were 1221.68 µg/mL, 2.69 µg/mL, and 15.15 µg/mL, respectively. Ethyl acetate-soluble part of metanolic extract was further investigated. It was partitionated using vacuum liquid column chromatoghraphy with different solvent system by increasing their polarities. There were three different fractions obtained. Fraction III exerted the highest inhibition activity with IC50 value of 1.33 µg/mL. It was separated subsequently to result four groups of compounds. III-C group presented the most potent inhibition activity with IC50 value of 0.7147 µg/mL. It was then subjected to preparative TLC and yieldedsix groups of subfractions. III-C-3 subfraction was indicated as the most potent compound with IC50 value of 0.3378 µg/mL. It was ten times weaker compared with antimitotic activity of Vincristine with IC50 of 0.0351 µg/mL. As a conclusian, ongkea cortex might have antimitotic property with the highest rate inhibition activity exhibited by III-C-3 compound. Keywords: ongkea cortex, Mezzettia Parviflora Becc, sea urchin eggs, antimitotic compound, antiproliverative activity